The open reading frame I (ORF I)/ORF II part of the human T-cell leukemia virus type I X region is dispensable for p40tax, p27rex, or envelope expression. - Roithmann, S (1994)
The X region of the human T-cell leukemia virus type I contains the second coding exon of the tax and rex regulatory proteins (open reading frame IV [ORF IV] and ORF III, respectively), as well as coding regions for more recently described proteins, p30II (or the tof protein) and p13II in ORF II and the putative rof protein and p12I in ORF I. Deletions and transcomplementation experiments showed that expression of the envelope, as well as that of the tax and rex proteins, was independent of the proteins encoded in the ORF I/ORF II region. Furthermore, p30II and p12I proteins could not replace the rex protein in a rex-dependent envelope or Gag protein expression system.